2019
DOI: 10.1177/2515841419864844
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal vein occlusion associated with platelet activation

Abstract: Purpose:The aim of this article is to determine and compare the platelet activation by three main platelet activation parameters: mean platelet volume, platelet distribution width, and plateletcrit in patients with central retinal vein occlusion and control subjects.Methods:This study included 30 patients with nonischemic central retinal vein occlusion and 30 control subjects. The levels of mean platelet volume, platelet distribution width, and plateletcrit were measured in all groups.Results:The mean serum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Mean platelet volume, a marker of platelet activation, has been investigated in patients with RVO, with a recent meta-analysis reporting that MPV is significantly elevated in patients with RVO compared to controls [ 7 ]. This is in line with the majority of studies [ 31 37 ], while Ornek et al observed lower MPV values in patients with RVO [ 38 ] and Turkseven Kumral et al observed unaffected indices [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…Mean platelet volume, a marker of platelet activation, has been investigated in patients with RVO, with a recent meta-analysis reporting that MPV is significantly elevated in patients with RVO compared to controls [ 7 ]. This is in line with the majority of studies [ 31 37 ], while Ornek et al observed lower MPV values in patients with RVO [ 38 ] and Turkseven Kumral et al observed unaffected indices [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Akpinar et al [20] increased PCT values were found effective in the development of saphenous vein disease after coronary bypass operations. In another study, PCT values were found to be higher in patients with central retinal vein occlusion than in healthy individuals [6]. The relationship of recurrent pregnancy loss with thrombosis is known.…”
Section: Discussionmentioning
confidence: 89%
“…Plateletcrit (PCT) is a parameter obtained by multiplying MPV with platelet count. In a recent study, PCT value was reportedly higher in patients with retinal vein thrombosis compared to the control group [6].…”
Section: Introductionmentioning
confidence: 87%
“…11 , 12 In addition, metformin, sulfonylureas, thiazolidinediones, and sitagliptin have also been shown to reduce platelet hyperactivity associated with diabetes and CRVO. 13 , 14 In contrast, basal insulin and sulfonylureas appear to be neutral on cardiovascular disease outcomes. 15 , 16 Given the association between cardiovascular risk and CRVO, these studies raise the important question as to whether systemic medications commonly used by diabetics may affect clinical features and outcomes in CRVO.…”
Section: Introductionmentioning
confidence: 99%